The role of nutrition and nutritional factors in the prevention and treatment of COVID19: a review study - Howra Bahrulolum; Saghi Nooraei; Maliheh Entezari; Mehrdad Hashemi; Kiavash Houshmandi; Mehdi Raei (فصلنامه ابن سینا, 2020)
Background: COVID-19 is a pandemic infectious disease caused by the Corona virus, has become a major global threat. The coronavirus mainly targets the human respiratory system. Cytokine storm and other altered immune responses have been shown to be associated with pathogenesis of diseases. The immune and the digestive systems both have been shared the important functions in terms of nutrients acquisition and host defense as gut microbiota. The main purpose of this study was to state the importance of healthy nutrition to boost immunity and its effect on the prevention and treatment of COVID-19. Materials and methods: In this review study, articles were collected by searching databases including PubMed, Google Scholar, Science Direct and Scopus using the keywords COVID-19 pandemic, Immunity system, Nutrients, and Nutritional supplement. Based on the inclusion and exclusion criteria, 82 qualified articles related to the subjected were evaluated. Results:  Micronutrients and macronutrients such as vitamins as well as other elements such as zinc, iron, selenium, and copper, proteins, and omega-3 long chain fatty acid play an important role in strengthening the immune system and increasing resistance to respiratory infections such as COVID-19. Conclusion:  A healthy diet to maintenance the host macro- and micro- nutrient and probiotics in food can be an effective and promising agent for the prevention and treatment of COVID-19 disease.